2020
DOI: 10.3389/fonc.2020.535449
|View full text |Cite
|
Sign up to set email alerts
|

KDM5c Promotes Colon Cancer Cell Proliferation Through the FBXW7-c-Jun Regulatory Axis

Abstract: KDM5c is a histone demethylase that specifically demethylates trimethylated and dimethylated H3 Lys-4 to play a central role in transcriptional repression. C-Jun is a proto-oncogene and promotes cell proliferation when ectopically accumulated, but can be ubiquitinated by SCF (FBXW7), leading to its degradation. FBXW7 is an E3 ubiquitin ligase of c-Jun, and exhibits carcinostasis in colon cancer. Here, we report that overexpression of KDM5c in human colon cancer cells results in attenuated FBXW7 transcription a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
16
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 21 publications
(16 citation statements)
references
References 31 publications
0
16
0
Order By: Relevance
“…FBXW7 exerts its role as a component of c-Jun’s E3 ligase, and knockdown of FBXW7 confers the accumulation of c-Jun ( 25 ). In colon cancer cells, the lysine demethylase KDM5c could attenuate FBXW7-mediated degradation of c-Jun by epigenetically modifying FBXW7 and decreasing FBXW7 transcription, further promoting cell proliferation ( 34 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…FBXW7 exerts its role as a component of c-Jun’s E3 ligase, and knockdown of FBXW7 confers the accumulation of c-Jun ( 25 ). In colon cancer cells, the lysine demethylase KDM5c could attenuate FBXW7-mediated degradation of c-Jun by epigenetically modifying FBXW7 and decreasing FBXW7 transcription, further promoting cell proliferation ( 34 ).…”
Section: Fbxw7 and The Hallmarks Of Cancermentioning
confidence: 99%
“…New evidence suggests that the dysregulation of KDM5 is related to important phenotypic consequences of various types of cancer [ 40 ]. For example, KDM5C promotes the proliferation of colon cancer cells through the FBXW7-c-Jun regulatory axis [ 20 ]. KDM5c inhibits the multidrug resistance of colon cancer cell lines by down-regulating ABCC1 [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
“…Studies have shown that abnormal expression of KDM5C is closely related to the occurrence and development of various cancers [ 18 , 19 ]. Overexpression of KDM5c in human colon cancer cells leads to weakened FBXW7 transcription and increases c-Jun protein, resulting in the proliferation of colon cancer cells [ 20 ]. In addition, KDM5C, which is highly expressed in PCa and CRPC, promotes the proliferation of castration-resistant prostate cancer (CRPC) cells through epigenetic inhibition of phosphatase and tensin homolog (PTEN) genes [ 21 ].…”
Section: Introductionmentioning
confidence: 99%
“…FBXW7 (F-Box and WD repeat domain containing 7, E3 ubiquitin-protein ligase of C-Jun) has been reported to be carcinogenic in colon cancer. Lin et al [ 35 ] reported that overexpression of lysine demethylase 5C reduced FBXW7 transcription and c-Jun protein accumulation, resulting in increased proliferation of human colon tumor cells.…”
Section: Discussionmentioning
confidence: 99%